2017
DOI: 10.1002/anie.201702905
|View full text |Cite
|
Sign up to set email alerts
|

Tailor‐made Molecular Cobalt Catalyst System for the Selective Transformation of Carbon Dioxide to Dialkoxymethane Ethers

Abstract: Herein a non-precious transition-metal catalyst system for the selective synthesis of dialkoxymethane ethers from carbon dioxide and molecular hydrogen is presented. The development of a tailored catalyst system based on cobalt salts in combination with selected Triphos ligands and acidic co-catalysts enabled a synthetic pathway, avoiding the oxidation of methanol to attain the formaldehyde level of the central CH unit. This unprecedented productivity based on the molecular cobalt catalyst is the first example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 45 publications
2
96
0
Order By: Relevance
“…Furthermore, the increasing availability of nonfossil energy technologies opens unique possibilities to tailor within this concept the interface of energy and material value chains. Conclusively, the incorporation of renewable energy in processes with the combined utilization of CO 2 and biobased carbon feedstock offers, in‐line with the principles of green chemistry, unprecedented synthetic pathways to carbon reduced fuels, chemicals and solvents, lately introduced as the “bio‐hybrid” approach …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the increasing availability of nonfossil energy technologies opens unique possibilities to tailor within this concept the interface of energy and material value chains. Conclusively, the incorporation of renewable energy in processes with the combined utilization of CO 2 and biobased carbon feedstock offers, in‐line with the principles of green chemistry, unprecedented synthetic pathways to carbon reduced fuels, chemicals and solvents, lately introduced as the “bio‐hybrid” approach …”
Section: Methodsmentioning
confidence: 99%
“…In 2017, a catalytic system for the direct hydrogenation of CO 2 to OME 1 based on a non‐precious transition metal catalyst could be established. In detail, various cobalt salts in combination with selected triphos ligands and acidic co‐catalysts enabled a straightforward direct synthesis of OME 1 via the formation of MF and MM intermediates. More specifically, Co(BF 4 ) 2 ·6H 2 O was employed as the most active cobalt precursor together with triphos ligand and Brønsted acid co‐catalyst HNTf 2 (bis(trifluoromethanesulfonyl)imide), leading to an active system for the formation of OME 1 with a TON of 373 starting from MF as substrate, and with a TON of 92 starting from CO 2 (Scheme ).…”
Section: One Step Synthesis Of Ome1from the Direct Hydrogenation Of Cmentioning
confidence: 99%
“…In addition, the versatility of the novel ruthenium‐ and cobalt‐catalyzed direct synthesis of OME 1 from CO 2 /H 2 and methanol was extended to the synthesis of dialkoxymethanes by replacing methanol with a variety of other alcohols. , Interestingly, reacting CO 2 /H 2 and ethanol resulted in diethoxymethane which is identified as a promising fuel candidate “bio‐hybrid fuel” from a production perspective. , …”
Section: One Step Synthesis Of Ome1from the Direct Hydrogenation Of Cmentioning
confidence: 99%
“…Other dialkoxymethanes could also be obtained by variation of the alcohol. In a subsequent study, it was shown that non‐precious transition metal systems based on cobalt can also be used to catalyze this reaction . These findings contribute to a better understanding of the catalysts and the underlying reaction mechanisms but scale‐up for the production of significant quantities is a major challenge.…”
Section: Recent Progress In Ome Productionmentioning
confidence: 99%